2019
DOI: 10.1093/carcin/bgz199
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal DNA methylation pattern and targeted therapy in colitis-associated cancer

Abstract: DNA methylation plays a crucial role in the pathogenesis of various diseases, including colorectal cancer (CRC). However, the global and temporal DNA methylation pattern during initiation and progression of colitis-associated cancer (CAC) are still unknown, including the potential therapeutic strategy of targeting methylation for CAC. In the present study, the global DNA methylation pattern was determined at different time points during CAC using DNA methylation sequencing, followed by the Starburst plot integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This specificity largely reflects the inter-tumor heterogeneity of the transcriptomic influence on cancers and the tissue distinction in cancer prognosis [75], implying that mediated pathways of the epigenomic impact vary cancer by cancer although DNA methylation pervasively regulates gene expression. It also has important implication on targeted therapies of precision cancers medicine by intervening DNA methylations [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…This specificity largely reflects the inter-tumor heterogeneity of the transcriptomic influence on cancers and the tissue distinction in cancer prognosis [75], implying that mediated pathways of the epigenomic impact vary cancer by cancer although DNA methylation pervasively regulates gene expression. It also has important implication on targeted therapies of precision cancers medicine by intervening DNA methylations [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation status sequencing at different time points during colitis-associated cancer (CAC) revealed that 811 genes were hypermethylated at different time points during CAC initiation and progression. These hypermethylated genes, including BAD and inositol polyphosphate phosphatase-like 1 ( INPPL1 ) hub genes, are involved in the MARK and EGF/EGFR pathways [ 112 ]. Tumor growth and drug response were assessed in PANC-1 cells (pancreatic ductal adenocarcinoma, PDAC) after exposure to a noncytotoxic dose of azacitidine.…”
Section: Experimental Studies On the Effects Of Combination Therapies Using Dnmt Inhibitorsmentioning
confidence: 99%
“…Some research has demonstrated that DNA methylation plays an important role in various biological processes (Luo et al, 2018), such as attaching transcriptional regulation (Poh et al, 2016) and functioning in diverse genomic partitions and developmental stages (Zhou et al, 2018). Li et al (2020) proposed that upregulated writers (DNMT1, DNMT3A, and DNMT3B) facilitated hypermethylation and downregulation of BAD and INPPL1 in colitis-associated cancer. Xu et al (2019) recommended TET2 (eraser) activity as a biomarker to predict the efficacy of anti-PD-1/PD-L1 treatment and patient response and the stimulation of TET2 activity as adjunct immunotherapy for CC.…”
Section: Introductionmentioning
confidence: 99%